GENDER SPECIFICITY OF THE FORMATION OF YOUTH LIFE POSITIONS IN THE GLOBAL INFORMATION ENVIRONMENT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
The rapid development of the global information environment has significantly transformed the worldview, social behavior, values, and life positions of young people. In the modern digital era, information technologies, social networks, virtual communication, and global media platforms have become the main factors influencing youth consciousness and socialization. At the same time, the impact of the information environment on young people differs according to gender characteristics, social roles, cultural norms, and opportunities for participation in digital space. This article analyzes the gender-specific aspects of the formation of youth life positions in the global information environment from a sociological perspective. The research examines the influence of digital media, online communication, information consumption, cyber risks, gender stereotypes, and digital inequality on young men and women. The article also explores international experiences and the socio-cultural conditions of Uzbekistan in shaping youth life positions under globalization. The study is based on sociological theories, comparative analysis, gender approaches, and contemporary empirical data. The findings demonstrate that the information environment simultaneously creates new opportunities for self-realization and new risks related to identity, values, and social adaptation. The article emphasizes the necessity of inclusive gender-sensitive approaches in developing youth policy and media literacy.